The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10820-006-9036-7
|View full text |Cite
|
Sign up to set email alerts
|

Dipole and solenoidal magnetic moments of electronic surface currents on toroidal nanostructures

Abstract: The time-dependent Schrödinger equation is developed for a spinless electron which is confined to move on a toroidal surface and curvature effects are taken into account. The electron motion is driven by linearly or circularly polarized microwaves including an interference field. To calculate the magnetic moments which are induced by the electronic surface currents on the torus an eight-state basis set is used. The system is driven at a resonance frequency to allow for transitions between states with opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…the torus lieing flat on the two planar leads will allow an increase in the number of metal-carbon contact sites and possibly lead to better and closer lead attachment. This could prove to be very interesting in the context of an applied microwave field with an additionally tilted static magnetic field due to the interplay between electronic excitations and persistent and bias-driven currents through the torus [40,41,42]. It is conceivable that quantum control applications could follow when the induced dipole and solenoidal magnetic moments couple to electronic spin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the torus lieing flat on the two planar leads will allow an increase in the number of metal-carbon contact sites and possibly lead to better and closer lead attachment. This could prove to be very interesting in the context of an applied microwave field with an additionally tilted static magnetic field due to the interplay between electronic excitations and persistent and bias-driven currents through the torus [40,41,42]. It is conceivable that quantum control applications could follow when the induced dipole and solenoidal magnetic moments couple to electronic spin.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the efforts directed towards quantum rings have focused on flat two-dimensional structures [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39]. While these objects can be more easily modelled in comparison to their toroidal counter parts, toroidal structures allow for motions around their minor radius in addition to azimuthal motion, which could give rise to novel phenomena [40,41,42]. Some of the potential applications by which the unique transport features of nanoscale tori might be exploited are:…”
Section: Introductionmentioning
confidence: 99%
“…However, to include the curvature potential as a function of λ, it would be necessary to find φ(λ) along the curve. While this could be accomplished numerically, using the azimuthal angle is somewhat better suited to incorporating external fields [29,30].…”
Section: Constructing the Effective Hamiltonianmentioning
confidence: 99%
“…Many studies have been conducted to investigate the structural models of tori CNTs to investigate their thermodynamic stabilities. The work of Ihara et al showed that the tori CNTs are found to be more stable than the C 60 fullerene, comparing the cohesive energies. , Additionally, many numerical simulations have demonstrated that the toroidal SWNTs (TSNs) exhibit quantum interference effect in charge transport under an external magnetic field or electromagnetic field, along their potential use as a macroscopic molecular toroid/coil with the molecular Aharonov–Bohm oscillator, spin-polarized current injector, detection of biopolymers, and metal–insulator transition switching. Recently, gold nanoparticles (Au NPs) were deposited on CNT rings for theragnostic applications . Nevertheless, the experimental studies and applications of TSNs have been dilatory as the theoretical investigations .…”
Section: Introductionmentioning
confidence: 99%